Probiotics as technological innovations in psychiatric disorders: patents and research reviews - Lima, Alyne Almeida de; Santos, Sthefane Silva; Araújo, Mykaella Andrade de; Vinderola, Gabriel; Villarreal, Cristiane Flora; Viana, Max Denisson Maurício (Frontiers in Nutrition, 2025)
Probiotics have shown promising results in treating anxiety and depression by modulating the gut-brain-microbiota axis using probiotics, which has motivated increasing commercial and academic interest in innovations and the probiotic market. This work explored innovation trends in the use of probiotics in the management of anxiety and depression, through a patent search performed in the Espacenet patent database. To expand the discussion, an additional search was performed on ClinicalTrials.gov and ScienceDirect. Recently probiotic innovations developed were deposited as pharmaceutical products (24.1%), functional foods (20.4%), or both (51.8%). Probiotic strains showed anxiolytic, antidepressant or both effects related to one or more mechanisms including modulation of neurotransmitters (61.1%), neuroendocrine mediators (35.2%) or neuroinflammation and oxidative stress (20.3%). The effects mainly were related to strains of the Lactobacillus (48.1%) and Bifidobacterium (38.9%) genera. In an additional search, 1,945 scientific publications and 11 clinical trials were found. Despite the efficacy observed in preclinical and clinical studies, transitioning from academic discoveries to patented innovations is not always straightforward. This review provides evidence for therapeutic applications of novel probiotic technologies in treating psychiatric disorders. It supports further studies exploring their benefits and highlights the need for greater investment in innovation in this area.